Response-related factors in reaction time to stimulus onset and offset tasks - Sokolova, R.; Rukšėnas, O.; Burle, B. (Psichologija, 2013)
According to V. Di Lollo et al. (2000), the difference in reaction time to stimulus onset and offset is related to response suppression. By using electromyographic activity recording, in the first experiment, we investigated whether both premotor and motor parts are affected by the task. Furthermore, in the second experiment, we investigated how other response-related factors, such as response type, could contribute to the difference between reaction time to stimulus onset and offset. In the first experiment, eleven subjects 29 ± 4.6 years old (six women and five men) performed reaction time tasks to stimulus onset and offset, and their response-related muscular activity was recorded. Sixteen 21.6 ± 1.5 years old subjects (eight women, eight men) participated in the second experiment, in which two types of responses were required. The results have revealed that differences in the reaction time to stimulus onset and offset are independent of response type and are related to the premotor part of reaction time only.